2018
DOI: 10.1093/annonc/mdy124
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance imaging with FDG-PET/CT in the post-operative follow-up of stage 3 melanoma

Abstract: Application of sub-stage-specific PET in stage 3 melanoma enables asymptomatic detection of most recurrences, has high NPVs that may provide patient reassurance, and is associated with a high rate of detection of resectable and potentially curable disease at relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 26 publications
(44 reference statements)
6
35
0
1
Order By: Relevance
“…Although costly, Podlipnik et al concluded recently that 6‐monthly surveillance CT scans were cost‐effective in stages IIB, IIC, and III patients for the first 3 years after diagnosis. Of note, although uncommon, curable secondary malignancies may be incidentally discovered (reported 6% in a melanoma surveillance series with PET) during posttreatment serial imaging, which is an ancillary benefit …”
Section: Surveillance Modalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although costly, Podlipnik et al concluded recently that 6‐monthly surveillance CT scans were cost‐effective in stages IIB, IIC, and III patients for the first 3 years after diagnosis. Of note, although uncommon, curable secondary malignancies may be incidentally discovered (reported 6% in a melanoma surveillance series with PET) during posttreatment serial imaging, which is an ancillary benefit …”
Section: Surveillance Modalitiesmentioning
confidence: 99%
“…There are few data on PET/CT in melanoma surveillance, and a wide range of opinions regarding utility have been published. Three recent retrospective reports, each with between 170 and 370 stage II or III patients, found an imaging surveillance regimen involving PET/CT detected 50% to 69% of recurrences, with median follow‐up ranging approximately 2 to 4 years . In another, a single PET/CT at a median of 7 months detected 24% of all recurrences .…”
Section: Surveillance Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Blank et al suggested a 'cancer immunogram' wherein a combination of biomarkers such as tumoral mutational load, presence of T-cell checkpoints, soluble cytokines, metabolic factors and host immune factors should be considered. Here we explore how existing non-invasive functional imaging might provide a readily translatable source of novel biomarkers, given the current increase of 18 F-fluorodeoxyglucose positron emission tomography/computerised tomography (FDG PET/CT) in the surveillance of high-risk melanoma [12] or at suspected relapse [13]. 18 F-fluoro-deoxy-glucose positron emission tomography (FDG PET) has long been the preferred functional imaging technique in melanoma in our facility [14].…”
Section: Introductionmentioning
confidence: 99%
“…This makes the population more heterogeneous and might influence the recurrence risk. It could be one reason for the slightly lower number of recurrences (30%) than the 38% reported in a recent published study that used routine, substage‐specific stage III PET/CT scanning schedule . Secondly, the present study cannot determine the exact survival gain associated with earlier stage IV diagnosis, or the effect of lead‐time bias.…”
Section: Discussionmentioning
confidence: 57%